1993
DOI: 10.2307/3578400
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Pneumonitis in Rats and Its Modification by the Angiotensin-Converting Enzyme Inhibitor Captopril Evaluated by High-Resolution Computed Tomography

Abstract: Adult male Sprague-Dawley rats were irradiated to the right hemithorax with a range of total doses delivered in 10 equal daily fractions of 4 MeV X rays. Half of each dose group consumed control feed, and half consumed feed containing the angiotensin-converting enzyme inhibitor captopril (50 mg/kg/day) continuously after the last irradiation. High-resolution computed tomography (CT) of the entire thorax was performed at 4 and 8 weeks after the last irradiation, and the findings with CT were correlated with hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Amifostine has been shown to protect against increases in breathing rate, increased plasma TGF-β, and fibrosis but is also known to interfere with chemotherapeutics [124][125][126][127]. Studies of angiotensin converting enzyme (ACE) inhibitors and angiotensin II receptor blockers, such as captopril, have shown significant protection against radiation pneumonitis and fibrosis [128][129][130][131][132][133]. Captopril is believed to reduce the effects of radiation on endothelial cells, fibroblasts and macrophages, and regulate the blood pressure of the pulmonary artery thus lowering edema in the lung.…”
Section: Protection Against Lung Inflammationmentioning
confidence: 99%
“…Amifostine has been shown to protect against increases in breathing rate, increased plasma TGF-β, and fibrosis but is also known to interfere with chemotherapeutics [124][125][126][127]. Studies of angiotensin converting enzyme (ACE) inhibitors and angiotensin II receptor blockers, such as captopril, have shown significant protection against radiation pneumonitis and fibrosis [128][129][130][131][132][133]. Captopril is believed to reduce the effects of radiation on endothelial cells, fibroblasts and macrophages, and regulate the blood pressure of the pulmonary artery thus lowering edema in the lung.…”
Section: Protection Against Lung Inflammationmentioning
confidence: 99%
“…Less data are available concerning the use of lung CT in smaller animals, for which spatial and contrast resolution are limited. Lung CT, however, has been performed in rats for the evaluation of radiation-induced lung injury, but only lung density was considered, and radiological patterns were not precisely described [12,18,19]. In the present study, it was demonstrated that dual-helical lung CT is efficient for the detection of pulmonary sarcoid-like granulomas in the rats injected with CFA.…”
Section: Discussionmentioning
confidence: 71%
“…Measurement of the mean lung density has previously been used to study radiation induced lung injury in rats [12,18,19]. This index, however, is relatively crude and results can be influenced by many factors, including the lung area scanned and the age of the animal [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that protective effect of angiotensin-converting enzyme (ACE) inhibitors and angiotensin II (AII) type 1 receptor blocker from RP is a topic of considerable interest [14,23]. Several groups reported that ACE inhibitors especially captopril and AII type 1 receptor blocker were effective in protecting lungs from RP and the development of lung fibrosis in rat radiation injury [30][31][32]. The possibility remains that administration of ACE inhibitors and AII type 1 receptor blocker might have two beneficial effects: control of radiation-induced side effects and control of hypertension in the future.…”
Section: Discussionmentioning
confidence: 99%